EyeTry: AR eyewear virtual try-on system - Ramli, Muhammad Hafiz (2025)
Online eyewear shopping presents significant challenges, primarily due to the inability of users to physically try on eyeglasses, resulting in uncertainty, low customer confidence, and high return rates. To address these issues, this project proposes the development of an Augmented Reality (AR)-powered Virtual Try-On system that enables users to visualize eyewear in real-time, enhancing their shopping experience. Leveraging advanced AR technologies, including face tracking, 3D modelling, and AI-driven recommendations, the system provides personalized solutions tailored to individual preferences. The project adopts Agile methodology, emphasizing iterative development and user feedback to refine the application and meet user needs effectively. This solution aims to reduce product returns, boost user confidence, and enhance brand loyalty, offering a seamless and engaging alternative to traditional online eyewear shopping. By integrating AR with user-friendly design and robust database management, this innovative system represents a significant advancement in e-commerce, bridging the gap between online and in-store shopping experiences. The effectiveness of the EyeTry application was evaluated using the System Usability Scale (SUS) method. The results showed overwhelmingly positive feedback from users: 100% found the app easy to use and navigate, 98% expressed interest in continued use, and the majority disagreed with statements about the app being complex or inconsistent. These findings reflect the system’s strong usability, intuitive design, and high user satisfaction.